2019
DOI: 10.1016/j.isci.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A Likely Ancient Genome Duplication in the Speciose Reef-Building Coral Genus, Acropora

Abstract: Summary Whole-genome duplication (WGD) has been recognized as a significant evolutionary force in the origin and diversification of multiple organisms. Acropora , a speciose reef-building coral genus, is suspected to have originated by polyploidy. Yet, there is no genetic evidence to support this hypothesis. Using comprehensive phylogenomic and comparative genomic approaches, we analyzed six Acroporid genomes and found that a WGD event likely occurred ∼3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Each taxonomic group evolved multiple stefin and/or type 2 cystatin homologues, forming individual taxonomy-defined clades in the phylogeny. These paralogues probably arose by gene duplication [ 30 ] rather than by whole genome multiplication, as the only basal metazoans for which genome duplication has been suggested are members of the cnidarian genus Acropora [ 69 ]. Multiple out-paralogues found in cnidarians likely originated before cnidarian radiation while, in-paralogues, probably emerged after the speciation event.…”
Section: Discussionmentioning
confidence: 99%
“…Each taxonomic group evolved multiple stefin and/or type 2 cystatin homologues, forming individual taxonomy-defined clades in the phylogeny. These paralogues probably arose by gene duplication [ 30 ] rather than by whole genome multiplication, as the only basal metazoans for which genome duplication has been suggested are members of the cnidarian genus Acropora [ 69 ]. Multiple out-paralogues found in cnidarians likely originated before cnidarian radiation while, in-paralogues, probably emerged after the speciation event.…”
Section: Discussionmentioning
confidence: 99%
“…Two years later, Si-Tayeb et al reported the detection of nMMP-3 in human hepatocellular carcinoma cell line (HepG2) and the identification of a nuclear localization signal (NLS) within the structure of the protease [66]. Since then, the number of reported nMMPs has grown, with some MMP members being localized to the nuclei in a variety of different cells types, originating from normal tissues, cancers, infected cells, and in cells during disease progression (Table 1) [67][68][69][70][71]. For example, nMMP-2 was found in normal skin cells in the lower one-third of the epidermis, whereas in the tumor and pre-cancerous samples, it was predominantly in the upper layers of the skin suggesting that the protein may be expressed at the early stages of squamous cell carcinogenesis [72].…”
Section: Mechanistic Regulation Of Nuclear Mmpsmentioning
confidence: 99%
“…Apoptosis ↑ Human hepatocellular carcinoma, hepatocellular carcinoma cell line, peritumoral liver, liver myofibroblasts; Chinese hamster ovary cells [56,66] Cell migration ↑ Human normal, osteoarthritic chondrocytes [58] Immune response ↑ Human embryonic kidney epithelial cell line, macrophages [69] Not defined Human megakaryocytes [78] MMP-7…”
Section: Mmp-1mentioning
confidence: 99%
See 2 more Smart Citations